OKUL ÖNCESİ EĞİTİMDE YARATICI DRAMA İLE ÖĞRENMENİN ÖNEMİ. - GEZEN, Esra (International Anatolian Journal of Social Sciences / Uluslararasi Anadolu Sosyal Bilimler Dergisi, 2022)
This review emphasizes the importance of learning with creative drama and the process of preparation for education in pre - school education. In pedagogical approach, it is attracted the attention of many studies currently that creative drama encourpoes the child to meet school at an early age and as a preparation for the learning process. The effect of creative drama or game on the preparation for education comes from the fact that learning is nourished by life itself. Learning with creative drama is a phenomenon which finds place in both childhood and adulthood. This phenomenon emerges as a way to compete or commonly learning while having fun. The process of realizing the learning environments and the problems encountered through our own lives through drama motivates the child in the pre-school period as well as distracts the student from motivating and limiting effects of rote learning. Our review is trying to ground the place and importance of creative drama in pre-school education within a theoretical framework. İn addition to this, it will be tried to show the strong ties of the contemporary education approach to creative drama.